Cuestiones constitucionales de la responsabilidad de los medios de comunicación por publicidad engañosa (2012)
This article aims to identify the relationship between freedom of expression, asbroad right and the duty to transmit clear truthfuladvertising, translated in thenew figure created by Act 1480 of 2011, which blamed the media for the issueof misleading advertising